Single-cell transcriptomics of leukocyte-enriched human milk reveals a highly diverse and adapted myeloid compartment - Nadine Schrode; Xiaoqi Yang; Alisa Fox; Disha Chowhan; Claire DeCarlo; Kristin Beaumont; Rebecca L.R. Powell (PLoS ONE, 2026)
Human milk is a bioactive fluid containing maternal leukocytes that support infant immune protection and development. Prior work has demonstrated the presence of atypical, non-granulocyte milk myeloid cells that do not conform to previously-defined cell subsets. To assess the true diversity of mononuclear milk myeloid cells, we performed single-cell RNA sequencing (scRNAseq) on >23,000 CD45 ⁺ enriched cells from 9 healthy lactating donors. Clustering identified 18 transcriptionally distinct mononuclear myeloid subpopulations, including 10 macrophage clusters, 5 dendritic cell subsets, 1 monocyte population, and 2 epithelial-like clusters. Macrophages segregated into M1-like and M2-like states exhibiting discrete transcriptional programs. The epithelial-like clusters expressed both epithelial markers (e.g., EPCAM, KRT19, CLDN3) and myeloid genes, suggesting phagocytic activity or hybrid states. Numerous myeloid sub-clusters exhibited transcriptional features consistent with adaptation to the lipid-rich environment of milk, supported also by reactome data. This included LDL and lipoprotein clearance pathways and expression of genes such as INSIG1 and QSOX1 in monocytes and APOE, LIPA, and APOC1 in macrophages. Signaling pathways were also dominated by degranulation and IL-4/10/13 activities, as well as antigen presentation programs. CellChat analysis revealed extensive intercellular communication among myeloid subsets involving MHC-II, SPP1, and MIF, consistent with active antigen presentation and tissue remodeling. Notably, pronounced donor-specific heterogeneity was observed, with several sub-clusters restricted to 1–2 individuals, underscoring personalized immune composition during lactation. These data indicate that milk myeloid cells are not merely passively transported immune cells but actively shaped and diversified by the lactational niche, and establish a high-resolution framework for future studies.